Effects of nitrogen application amount on nitrogen distribution and photosynthesis in tea leaves - Li, Kai; Liu, Dong-Na; Li, Lan-Ying; Gao, Yuan; Gao, Wan-Jun; Chen, Bo-Wen; Luo, Fan; Yao, Yu (Frontiers in Plant Science, 2025)
Nitrogen is the most essential nutrient for plant growth and serves as a key limiting factor in overall plant development. Photosynthesis is the primary process for energy capture in the biosphere, and its effectiveness is significantly influenced by the nitrogen content and distribution within leaves. In this experiment, the yellow tea variety “Jinfeng No. 2” (hereinafter referred to as JF) and the green tea variety “Fuding Da Bai Tea” (hereinafter referred to as FD) were utilized as experimental materials. Five nitrogen levels were established to investigate the effects of varying nitrogen levels on leaf characteristics, including photosynthetic physiology, leaf nitrogen allocation, and photosynthetic nitrogen use efficiency in tea plants. The results demonstrated that the net photosynthetic rate and photosynthetic nitrogen use efficiency of both tea cultivars initially increased and then decreased with rising nitrogen levels. As nitrogen levels gradually increased, the nitrogen content in the carboxylation and electron transport systems for both tea varieties first rose and then declined. Specifically, nitrogen content in the light capture system of FD increased initially but then decreased, while in JF, it exhibited a steady increase. Additionally, nitrogen content in the structural system increased slowly, whereas that in the storage system rose significantly. With increasing nitrogen levels, the distribution ratio of leaf nitrogen in the carboxylation and electron transport systems initially increased and then decreased; in the structural system, it first decreased and subsequently stabilized, while in the storage system, it gradually increased. In the light capture system, the two varieties displayed different trends: FD’s nitrogen distribution decreased, while JF’s increased. Our results indicated that within a certain range, increasing nitrogen levels can significantly enhance the photosynthetic capacity of tea plants and improve photosynthetic nitrogen use efficiency. However, at high nitrogen levels, the reduction in nitrogen content and the proportion allocated to the photosynthetic system, along with the increase in nitrogen content and proportion allocated to non-photosynthetic systems, were the primary factors contributing to the decline in net photosynthetic rate and photosynthetic nitrogen use efficiency. By increasing the nitrogen content in the carboxylation and electron transport systems, tea plants can achieve enhanced photosynthetic capacity.